Surgical Site Infections at the General Referral Hospital of Niamey, Niger - Nana, Félicité Wendin-manegdé; Soumana Zataou, Abdourahamane; BA, Absatou; Hien, Herve; Poda, Gislain Gnimbar; Belemsaga, Danielle Yugbare; Drabo, Maxime Koine (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2025)
Introduction: Surgical site infections (SSIs) are a significant cause of morbidity, driven by surgical practices and the increasing prevalence of antimicrobial-resistant pathogens. This study aimed to estimate the prevalence of SSIs at the General Referral Hospital of Niamey in 2023, characterize the affected patients, and analyze the isolated pathogens and their antimicrobial resistance profiles.Methods: A retrospective descriptive study was conducted on 1,625 medical records from digestive surgery, trauma orthopedics, neurosurgery, and intensive care units in 2023. SSI cases were identified using the national clinical criteria, and microbiological data were extracted from laboratory reports. Data were extracted from registers, medical records, nursing care files, and laboratory databases. Data validation and reliability assurance were performed through double data entry, completeness and consistency checks, and data collector training.Results: The SSI prevalence was 1.7% (28 cases), predominantly in trauma orthopedics and neurosurgery (36%). Among the 26 isolates, gram-negative bacilli represented 69%, mainly Escherichia coli (27%) and Pseudomonas spp. (15%). Gram-positive cocci accounted for 31% of cases, with Staphylococcus aureus (27%). Antimicrobial susceptibility testing (24 isolates) showed high resistance to third-generation cephalosporins (40–80%), presence of ESBL-producing Enterobacterales, and one MRSA isolate. Carbapenems remained highly effective (>90%), whereas fluoroquinolones exhibited moderate activity (40–60%).Conclusion: The predominance of multidrug-resistant gram-negative bacteria underscores the need to strengthen infection prevention and control measures, optimize antibiotic prophylaxis, and enhance microbiological surveillance within surgical units